Using Phenomenography to Tackle Key Challenges in Science Education - Han, Feifei; Ellis, Robert A. (Frontiers in Psychology, 2019)
This article describes how phenomenography, as a qualitative research method, can be used to tackle key challenges in science education. It begins with an overview of the development of phenomenography. It then describes the philosophical underpinnings of phenomenographic inquiry, including ontological and epistemological roots, and its unique second-order perspective. From theoretical background to practicality, the paper uses rich examples to describe in detail the procedures of conducting a phenomenographic study, including sampling and data collection, analyzing phenomenographic data, and communicating key findings. The paper concludes by showing how the phenomenographic method can be used to develop students’ conceptual understanding of scientific concepts, to inform effective instructional design in science teaching, and to identify and improve evidence-based factors in student learning to enhance learning outcomes in science.